Deskripsi Kemampuan Berpikir Kreatif Matematis Siswa dalam Menyelesaikan Soal Materi Bangun Datar - Tahir Tahir; La Ode Sirad; Chairuddin Chairuddin; Marniati Marniati (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2023)
This research was carried out with the aim of giving an overview to KBKM students in solving problems related to flat shapes. The type of research used is descriptive qualitative research. The research sample was selected using the cluster random sampling method and a sample of 22 students was obtained. The tools used in this study were tests and interviews. Descriptive analysis of research data, students' KBKM in completing questions on flat material, with an average score of 50 which is the same as the value in the quite creative category, 4 students in the criteria of very creative, creative and creative enough, 9 students in the criteria not less creative and 1 student on uncreative criteria. From the results of data analysis it can also be seen that the main problem of the students' KBKM in solving the first flat matter problem lies in the elaboration indicator, which from the results of data analysis and interviews it can be seen that in solving the questions students have difficulty in giving correct and detailed answers. students were not careful in working on the questions and some students were able to understand questions related to elaboration indicators. Furthermore, the second biggest problem lies in the authenticity indicator. In this indicator students have difficulty making answers using their own way, the majority of students are only able to follow the method exemplified by the teacher.